1992
DOI: 10.1063/1.461880
|View full text |Cite
|
Sign up to set email alerts
|

Spin–orbit configuration-interaction study of valence and Rydberg states of LiBe

Abstract: A b initio spin–orbit full configuration-interaction calculations in the context of relativistic effective core potentials are reported for the weakly bound metal dimer LiBe, a three-valence-electron system. The effects of basis set on the energies of valence and Rydberg states of the cluster are discussed, as are the effects of configuration space selection on the energy of the latter states. Results at the dissociative limit are compared to the experimental atomic spectra. Potential-energy curves and spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 19 publications
6
23
0
Order By: Relevance
“…The electronic structure of Ba neutral compounds (BaLi, BaNa, BaK) has been explored some time ago by Allouche and coworkers [38][39][40]. Other studies concern CaLi [41][42][43], LiBe [44,45]. More recently the electronic structure of the related molecular ions containing one alkali atom and Ca + [46], Sr + [47] or Ba + [48][49][50][51] with various high-level approaches have been published in relation with experiments aiming at creating cold molecular ions in merged cold ion and cold atom traps.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure of Ba neutral compounds (BaLi, BaNa, BaK) has been explored some time ago by Allouche and coworkers [38][39][40]. Other studies concern CaLi [41][42][43], LiBe [44,45]. More recently the electronic structure of the related molecular ions containing one alkali atom and Ca + [46], Sr + [47] or Ba + [48][49][50][51] with various high-level approaches have been published in relation with experiments aiming at creating cold molecular ions in merged cold ion and cold atom traps.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning this kind of molecule for which several theoretical studies have been reported, with results and predictions often quite contradictory, experimen-talists and theoreticians have recently focused specific attention on the study of their low-lying electronic states. 11,[14][15][16] With regard to the dissociative channels, these studies demonstrate that there is a need for high level ab initio investigations on the asymptotic long-range properties.…”
Section: Introductionmentioning
confidence: 92%
“…6,7 Nowadays, many ab initio calculations yield a slightly attractive ground state for LiBe and the beryllium dimer Be 2 . [8][9][10][11][12][13] Difficulties and differencies between the calculation are usually assigned to the quasidegeneracy of the 2s and 2p orbit- als of the Be atom. Highly sophisticated ab initio methods with very high angular moment basis functions are needed for the accurate calculation of the electronic structure and properties of these compounds.…”
Section: ͑4͒mentioning
confidence: 99%
See 2 more Smart Citations